Technical Assessment of Reusing Retired Electric Vehicle Lithium-Ion Batteries in Thailand - Phophongviwat, Teeraphon; Polmai, Sompob; Maneeinn, Chaitouch; Hongesombut, Komsan; Sivalertporn, Kanchana (My University, 2023)
A rapid growth in electric vehicles has led to a massive number of retired batteries in the transportation sector after 8–10 years of use. However, retired batteries retain over 60% of their original capacity and can be employed in less demanding electric vehicles or stationary energy storage systems. As a result, the management of end-of-life electric vehicles has received increased attention globally over the last decade due to their environmental and economic benefits. This work presents knowledge and technology for retired electric vehicle batteries that are applicable to the Thai context, with a particular focus on a case study of a retired lithium-ion battery from the Nissan X-Trail Hybrid car. The disassembled battery modules are designed for remanufacturing in small electric vehicles and repurposing in energy storage systems. The retired batteries were tested in a laboratory under high C-rate conditions (10C, 20C, and 30C) to examine the limitations of the batteries’ ability to deliver high current to electric vehicles during the driving operation. In addition, the electric motorcycle conversion has also been studied by converting the gasoline engine to an electric battery system. Finally, the prototypes were tested both in the laboratory and in real-world use. The findings of this study will serve as a guideline for the sorting and assessment of retired lithium-ion batteries from electric vehicles, as well as demonstrate the technical feasibility of reusing retired batteries in Thailand.
Keywords: disassembled battery module; electric vehicle; energy storage; lithium-ion battery; second-life application; technical feasibility